Statistical models for the mechanical properties of 3D printed external medical aids. Issue 1 (7th December 2020) - Moreno, Rafael; Carou, Diego; Carazo-Álvarez, Daniel; Gupta, Munish Kumar
Abstract : Purpose: 3D printing is gaining attention in the medical sector for the development of customized solutions for a wide range of applications such as temporary external implants. The materials used for the manufacturing process are critical, as they must provide biocompatibility and adequate mechanical properties. This study aims to evaluate and model the influence of the printing parameters on the mechanical properties of two biocompatible materials. Design/methodology/approach: In this study, the mechanical properties of 3D-printed specimens of two biocompatible materials (ABS medical and PLActive) were evaluated. The influence of several printing parameters (infill density, raster angle and layer height) was studied and modelled on three response variables: ultimate tensile strength, deformation at the ultimate tensile strength and Young's modulus. Therefore, statistical models were developed to predict the mechanical responses based on the selected printing parameters. Findings: The used methodology allowed obtaining compact models that show good fit, particularly, for both the ultimate tensile strength and Young's modulus. Regarding the deformation at ultimate tensile strength, this output was found to be influenced by more factors and interactions, resulting in a slightly less precise model. In addition, the influence of the printing parameters was discussed in the work. Originality/value: The presented paper proposed the use of statistical models to select the printing parameters (infill density, raster angle and layer height) to optimize the mechanical response of external medical aids. The models will help users, researchers and firms to develop optimized solutions that can reduce material costs and printing time but guaranteeing the mechanical response of the parts.